Trends in maternal mortality in Peru 2019 - 2023 - del Carpio Ancaya, Lucy (2024)
Introduction: Maternal mortality is a highly sensitive indicator of the living conditions,health and development of the population. Objective: To determine the situationof maternal mortality (MM) in Peru between 2019 and 2023, visualising the figuresand interventions. Material and methods. Information was reviewed from theMaternal Mortality Epidemiological Surveillance System of the General Directorateof Epidemiology of the Ministry of Health, the HIS System for the registration andcoding of information, and the Demographic and Family Health Survey for the years2021 to 2023. Results: A decrease in the number of maternal deaths (264 MM in 2023)and in the maternal mortality ratio (51.9 per 100,000 live births in 2023) in Peru hasbeen found. Direct causes od death are maintained, but in different percentages bynatural regions, with hemorrhage being the leading cause of maternal mortality. Thecoverage of care has increased in recent years, but it is still necessary to improve thecapacity for timely response and quality of health services. Conclusions: Althoughthere is evidence of a decrease in MM, it is necessary to strengthen the strategiesthat have been implemented to meet the Sustainable Development Goal 3 targeton reducing global maternal mortality to 70 per 100,000 live births. The maternalmortality reduction target set for Peru for 2030 is 41.3 per 100,000 live births.